DBS India: Banking on the unbanked - TAN, Swee Liang (Institutional Knowledge at Singapore Management University, 2019)
The case is set in 2015, when DBS Bank applied to the Reserve Bank of India to operate as a locally incorporated subsidiary under the wholly-owned subsidiary (WOS) scheme. DBS had a presence in India since 1995 and had grown to become the fifth largest foreign bank by assets. Upbeat about the growth prospects, it was the first foreign bank to apply for the conversion from branch operation to WOS. The scheme would extend near-equal treatment to locally-incorporated foreign banks as with national banks, and it aimed to incentivise them to scale up their operations in return for opening new branches in under-banked and unbanked cities and issuing credit to companies categorised under the priority lending sectors. However, the past year had been challenging for DBS India. Its profitability had taken a hit as bad loans rose more than four-fold, climbing to the top of the list among all private banks in India. The bad debts were primarily due to delayed servicing of loans by construction companies, which were granted credit during a previous period of aggressive lending. The case discusses the opportunities and challenges the WOS brings to DBS India, leading to its final decision to apply for the scheme. This case revolves around the growth decision of a foreign bank, through which the students will (1) gain an overview of the banking industry in India; (2) learn to differentiate between foreign banks and private domestic banks; (3) analyse the macro and micro implications of the WOS scheme on domestic and foreign banks; and (4) discuss the opportunities and challenges the WOS brings to DBS India, leading to its final decision to apply for the scheme.